1999
DOI: 10.1002/(sici)1520-636x(1999)11:7<522::aid-chir2>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective anion exchangers based on cinchona alkaloid-derived carbamates: Influence of C8/C9 stereochemistry on chiral recognition

Abstract: Four diastereomeric chiral stationary phases (CSPs) based on quinine, quinidine, epiquinine, and epiquinidine tert‐butyl carbamate selectors were synthesized and evaluated under ion exchange HPLC conditions with a set of racemic N‐acylated and N‐oxycarbonylated α‐amino acids as selectands. The enantioseparation potential of quinine‐ and quinidine‐derived CSPs proved to be far superior to that of their C9‐epimeric congeners. The absolute configuration of C9 stereogenic center of the cinchonan backbone of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 6 publications
4
98
2
Order By: Relevance
“…Although they are diastereomers, they are often termed "pseudoenantiomers" as it is observed that the configuration of C8/ C9 is predominantly responsible for molecular recognition of chiral compounds. 17,18 In this paper, we report the results of the enantioselective transport of D,L-phenylglycine and D,L-phenylalanine across a bulk liquid chloroform membrane by means of different commercial cinchona derivatives as carriers, selected in order to study the influence of their structure and nature on enantioselective transport ability. Some quaternary ammonium salts (selectors 4-7) have been included among the investigated cinchona alkaloids, in order to evaluate the contribution of ion-pair interaction in the analyte-carrier complex formation, which is supposed to be predominant over the other interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are diastereomers, they are often termed "pseudoenantiomers" as it is observed that the configuration of C8/ C9 is predominantly responsible for molecular recognition of chiral compounds. 17,18 In this paper, we report the results of the enantioselective transport of D,L-phenylglycine and D,L-phenylalanine across a bulk liquid chloroform membrane by means of different commercial cinchona derivatives as carriers, selected in order to study the influence of their structure and nature on enantioselective transport ability. Some quaternary ammonium salts (selectors 4-7) have been included among the investigated cinchona alkaloids, in order to evaluate the contribution of ion-pair interaction in the analyte-carrier complex formation, which is supposed to be predominant over the other interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Cinchonane-type derivatives such as 1 have found widespread use as selective separation agents ("chiral selectors") for discriminating the enantiomers of chiral acids, specifically, N-blocked amino acids [21,61,63]. Virtually every mode of liquid-phase enantioselective separation has been investigated (except supercritical chromatography) and the interaction mechanism has been well characterized [62,67,68].…”
Section: Resultsmentioning
confidence: 99%
“…Monovalent selector 1 was prepared following a procedure described previously [63]. Bivalent selector 2 was synthesized from quinine in six steps in 31% overall yield.…”
Section: Chemicals and Synthesismentioning
confidence: 99%
“…1. Since, these two molecules are not enantiomers but in fact diastereomers with 7 chiral centers, of which only those in positions 8, 9, 1 and 2 are inverted, they do not necessarily exhibit opposite elution orders in all cases [36,37]. The chiral centers of the quinuclidine residue (positions 1, 3 and 4) have the same configuration in both selector motifs.…”
Section: Chromatographic Selectivitymentioning
confidence: 99%